Kendala Budaya dan Bahasa dalam Kegiatan Ekspor-Impor di Indonesia - Endro Prihastono (Dinamika Bahasa dan Budaya, 2008)
This paper examines some issues with respect to language and cultural breakdowns in the Export-Import Activities. The writer simply outlines possible problems that may be faced by the exporters and importers, especially who operate in Indonesia. This is because Indonesian people, as one of the Asean members, are normally bound to the application of Indonesian culture in dealing with business across the globe. This of course would cause some cultural breakdowns which in turn influence the export-import activities in the form of cultural misunderstanding. Besides, the language (English) used in the Export-Import dealings is somehow different from the English people learn at schools or colleges. In short, this paper is hoped to open up the view of the importance of designing a special training of English for Export-Import business. Key words: Export-Import, cultural breakdowns, English for Export-Import business